An analysis of the determinants and recent decline of private savings in South Africa - Linde, Kathryn Leigh (Rhodes University, Faculty of Commerce, Department of Economics and Economic History, 2012)
Low domestic saving rates make South Africa highly dependent on foreign capital inflows to fund higher investment levels. These inflows are highly volatile and may prove to be unsustainable in the long-run. This study analyses the determinants of private saving in South Africa, with specific reference to the decline in private saving rates that occurred at a time of higher economic growth prior to the 2008 global financial crisis. The Johansen cointegration method is used to estimate separate vector error correction models (VECM) in order to assess the effect of specific variables on both corporate and household saving. The results obtained that are common to both corporate and household savmg show that the govemment budget balance negatively impacts private saving rates though the offset is less than one. The real prime overdraft rate positively impacts private saving, although the result is small . The impact of real Gross Domestic Product (GDP) is positive. In recent years, however, private saving rates fell alongside higher economic growth, which may reflect a structural change in corporate saving behaviour. The results distinct to the corporate saving model show that commodity prices have a negative impact on corporate saving. This does not conform to a priori expectations, but is supported by the behaviour of these two variables in recent years. Foreign savings were found to impact negatively on corporate saving. This result is important, since the dependence of the South African economy on foreign capital inflows to fund higher investment levels is reflected by high current account deficits during recent periods of economic growth. Evidence of financial liberalization negatively impacting on private saving in South Africa due to the removal of borrowing constraints was found. A negative relationship was found between corporate saving and investment demonstrating that corporations have reduced levels of retained eamings for funding investment expenditures. The results distinct to the household saving model provide evidence of a negative wealth effect in South Africa, with rising housing wealth found to increase consumption. Evidence of households "piercing the corporate veil" in South Africa was found. Therefore, households view corporate saving behaviour as essentially being conducted on their behalf. This finding and the finding that the offset between the budget deficit and private saving is less than one suggest that counter-cyclical fiscal policy will be an important policy response for achieving higher domestic saving rates in South Africa.
Keywords: Saving and investment -- Research -- South Africa; Finance, Personal -- Research -- South Africa; Corporations -- Finance -- Research -- South Africa; Economic development -- Research -- South Africa